Cover Jurnal EECCIS Vol 13 No.3 Desember 2019 - jurnal, Editor (Jurnal EECCIS (Electrics, Electronics, Communications, Controls, Informatics, Systems), 2019)
Cover Jurnal EECCIS Vol 13 No.3 Desember 2019